Student’s perceptions of the effectiveness on time management skills in assisting their online distance learning / Noraini Ahmad … [et al.] - Ahmad, Noraini; Mohd Khairi, Nurul Hanis; Hassanuddin, Nor Aini; Mamat, Siti Salwana; Rosly, Nur Syazana (Universiti Teknologi MARA, Perlis, 2023)
During the COVID-19 pandemic, many people all over the globe suffered from disorientation. The main identified cause is a sudden adaptation to remote working and learning, due to the abrupt closure of working and educational institutions. This includes the students at higher learning institutes who had to continue their studies through online distance learning (ODL) for almost two whole years., Time management skills are vital for students, and it becomes very crucial, especially in the critical time of the pandemic, to ensure the continuity of their learning process. The aim of this research is to study the relationship between time management skills with the level of productivity and motivation during open and distance learning (ODL). A quantitative approach was used as the mode of research. The students from the Faculty of Education were taken as sample respondents. The collected data were analyzed through SPSS Statistics software using descriptive analysis, chi-square, and simple linear regression. The results found a significant influence and relationship between time management skills and the students’ productivity and motivation levels. Overall, this research was able to answer some questions regarding the student’s time management skills during their ODL and how it affected their whole performances.